Effect of Remineralizing Agents on Shear Bond Strength of Orthodontic Brackets-In Vitro Study - Alexandrina Muntean; Cristina-Maria Dârgău; Mariana Pacurar; Simina Neagoe; Ada Gabriela Delean (MDPI AG, 2023)
Orthodontic treatment can be effective only with the proper adhesion strength of the bonded elements on the teeth. The aim of the study was to analyze the influence of different remineralization products on the brackets (Evolve Low Profile Brackets 0.022 Roth prescription (DB Orthodontics Ltd., Silsden, England) shear bond strength (SBS)). In all, 40 teeth were investigated for this study; n = 30 demineralized (immersed in 0.1% citric acid for 30 min, twice a day, for 20 consecutive days) and n = 10 immersed only in artificial saliva. After the demineralization process, remineralization agents were applied to each group (n = 10): Group I: Elmex Sensitive professional® toothpaste (CP, Gaba GmbH, Witten, Germany) and GC MI Paste Plus® (GC, Leuven, Belgium), Group II: Elmex Sensitive professional® toothpaste (CP, Gaba GmbH, Germany) and GC Tooth Mousse® (Leuven, Belgium), Group III: Elmex Sensitive professional® toothpaste (CP, Gaba GmbH, Germany). For the teeth in control group C, Elmex Sensitive professional® toothpaste was used. SBS tests were performed by means of an advanced materials-testing machine that generated maximum load and tensile strength values. The data obtained underwent statistical analysis (ANOVA and Tuckey test) with a statistical threshold of p < 0.05. The SBS values were higher for group II (14.20 MPa) and I (10.36 MPa) and lower for group III (4.25 MPa) and C (4.11 MPa), with statistically significant differences between groups I and II when compared with groups III and C (p < 0.05). In conclusion, GC Tooth Mousse® and MI-Paste Plus® have no adverse effect on brackets SBS and are recommended to be used for enamel remineralization during orthodontic treatment.